The Influence of Education Curriculum, Motivation, and Parenting Patterns on The Competence of Cadets in Banten Shipping Polytechnic - Irma Natalia; Setyo Riyanto (Jurnal Indonesia Sosial Teknologi, 2022)
The quality of human resources, one of which is determined by the education factor, has a very important strategic role in determining the progress and success of a country. Talking about Indonesia's development, of course, cannot be separated from Indonesian education in the eyes of the world. Education is one of the important factors of the authority of a country. With a good education, of course, it will produce the next generation of people who are smart and competent in their respective fields. So that the state of the country will continue to improve along with the emergence of successors of the state from all walks of life. This study aims to determine and analyze the effect of educational curriculum, motivation, and parenting patterns on the Competence of the Banten Shipping Polytechnic Cadets. The research was conducted at the Banten Shipping Polytechnic with a research time of March 2022 to June 2022. The method used is a quantitative analysis approach through data collection techniques using questionnaires. The population studied was the Banten Shipping Polytechnic cadets in 2020, with a sample of 394 respondents. The sampling method used probability sampling with a simple random sampling technique—the method of analysis for hypothesis testing with the help of software SmartPLS 3.2.9. The analysis results show that the educational curriculum, the motivation, and the pattern of caregivers have a positive and significant effect on the competence of the Banten Shipping Polytechnic cadets. The original sample results show the influential factors, where the competence of the cadets is strongly influenced by motivation. Motivation is much influenced by the encouragement of learning needs in the Parenting Pattern. It is concluded that the education curriculum, especially the competency approach, is highly related to the educational curriculum. The highest motivation comes from the need to learn, which means cadets are motivated by the need to learn. The pattern of caregivers, especially suggestive (the method used to provide encouragement or support in the form of views, suggestions, and advice for a more interactive communicative atmosphere), has a high relationship with the pattern of caregivers.